2008
DOI: 10.1080/13576500802249538
|View full text |Cite
|
Sign up to set email alerts
|

The lighter side of advertising: Investigating posing and lighting biases

Abstract: People tend to display the left cheek when posing for a portrait; however, this effect does not appear to generalise to advertising. The amount of body visible in the image and the sex of the poser might also contribute to the posing bias. Portraits also exhibit lateral lighting biases, with most images being lit from the left. This effect might also be present in advertisements. A total of 2801 full-page advertisements were sampled and coded for posing direction, lighting direction, sex of model, and amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…A large majority of photographs and portrait paintings have been discovered to depict scenes in which illumination comes from above—which is not surprising—and from the left, the reasons for which are far less obvious (Sun and Perona, 1998; McManus et al, 2004; Thomas et al, 2008). If lighting preference is equated with the frequency of its representation then by this convention there is a partial dissociation between the effect of lighting direction on perceived intensity and preference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large majority of photographs and portrait paintings have been discovered to depict scenes in which illumination comes from above—which is not surprising—and from the left, the reasons for which are far less obvious (Sun and Perona, 1998; McManus et al, 2004; Thomas et al, 2008). If lighting preference is equated with the frequency of its representation then by this convention there is a partial dissociation between the effect of lighting direction on perceived intensity and preference.…”
Section: Discussionmentioning
confidence: 99%
“…When interpreting the shape of ambiguous 3D surfaces the visual system exhibits a bias that directional illumination is mostly from above (Ramachandran, 1988; Sun and Perona, 1996a,b, 1998; Mamassian and Goutcher, 2001; Stone et al, 2009; de Montalembert et al, 2010; Morgenstern et al, 2011; Schofield et al, 2011; Andrews et al, 2013) and slightly from the left (Sun and Perona, 1998; Mamassian and Goutcher, 2001; Mamassian et al, 2003; McManus et al, 2004; Thomas et al, 2008; de Montalembert et al, 2010; Andrews et al, 2013). The light-from-above bias is well illustrated by experiments demonstrating that discs with top-dark luminance gradients are seen as concavities while those with top-bright luminance gradients are perceived as convexities (Ramachandran, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Although the leftward posing bias is widespread, there are certain contexts in which this bias disappears. For example, advertising images show mixed posing biases, where it has been found that women still exhibit a leftward posing bias, but men do not (Thomas, Burkitt, Patrick, & Elias, 2008a), or that posing of both men and women shifts to a rightward bias (Burkitt, Saucier, Thomas, & Ehresman, 2006). The leftward posing bias also disappears in Buddhist artwork (Duerksen, Friedrich, & Elias, 2016) and decreases in images of science academics (Churches et al, 2012).…”
mentioning
confidence: 95%
“…It has been argued that a stimulus is perceived as face-like only if it appears with the correct luminance, similar to a face under (natural) top-lit illumination (Farroni et al, 2005; Salva et al, 2012), and that the right hemisphere might play a crucial role in this kind of social orienting responses (Salva et al, 2012). We propose that perhaps this is due to a social orienting bias in perception: portraits, photographs, and advertisements are normally lit from the left rather than from the right (McManus et al, 2004; Thomas, Burkitt, Patrick, & Elias, 2008), and artists prefer to locate the light at an angle left of the vertical when illuminating paintings (McDine, Livingston, Thomas, & Elias, 2011), which in turn can create a more favorable purchase intention in customers (Hutchison, Thomas, & Elias, 2011). Orientation perception does not influence only information processing efficiency and social orienting responses, but the aesthetic preference for a particular arrangement of stimuli or pictures as well.…”
Section: Introductionmentioning
confidence: 99%